(untitled) (AYUSHDHARA, 2018)
Pakshaghata is one among the Vatavyadhis. It similar to biomedical cerebrovascular condition called ‘stroke’. The Lakshanas include Ruja, Vakstambha etc. Its types are Kaphanubandha and Pittanubandha. Even though Pakshaghata is a Vata vyadhi and mentioned in the Nanatmaja Vatajavikaras of Charaka, it is not a Shuddha vataja condition. There is Samsarga of Pitta and Kapha, clearly mentioned by Susrutha and Madhava nidana. In all the above explanations it is clear that Raktadushti leading to Vata prakopa is the underlying cause of the disease. Third most important cause for death worldwide is Cerebrovascular accidents and one among every 10 deaths is due to acute stroke. Signs and symptoms of acute stroke can be taken as Pakshaghata, which is one among 80 types of Nanatmaja Vata vikaras, since Kevalavata vyadhis are difficult to cure Ayurveda is showing global opportunities as the patients suffer from physical disability even after the latest treatment. So here is an effort is done to show the role of Avapeedana nasya in the management of Pakshaghta. The data of 6 patients was collected irrespective of sex and religion. Statistical analysis done by using paired ‘t’ test which has shown highly significant result.